Reducing the clogging of emitters in drip irrigation systems using acid washing and ultrasonic technology - Hossein Dehghanisanij; Seyed Majid Mirlatifi; Somayeh Emami; Tahereh Rajabzadeh (Scientific Reports)
Abstract The main challenge in maintaining drip irrigation systems is the emitter’s clogging. In this study, the acid-washing method was used to remove chemical blockages, while ultrasonic technology was employed to reduce physical and biological deposits in emitters. These methods improve the performance of drip irrigation systems, increase water productivity and reduce maintenance costs. Emitters were collected from the field and divided into five groups (100%, 100–75%, 50–75%, 50–25%, and 0–25% clogging) based on discharge. Then, four treatments were applied to each group: acidic-washing with pH = 3 (T1), acidic- washing with pH = 5 (T2), ultrasonic washing (T3), and a combination of ultrasonic and acid-washing (T4). 98% sulfuric acid was chosen for acid-washing due to its cost-effectiveness. The results showed that acid-washing with pH = 3 was more effective than pH = 5, especially for emitters with more than 75% clogging, which were mainly chemical clogging. Ultrasonic washing was more effective in clogging more than 50% and its effectiveness increased with increasing clogging intensity. The results showed that ultrasonic technology, as a non-chemical alternative method, along with acid-washing, has a significant effect in reducing blockages and can be an effective and sustainable solution for irrigation management. In general, the findings of this research can help farmers and managers of irrigation systems to increase the productivity of water resources and reduce maintenance costs by choosing appropriate approaches. In addition, the use of non-polluting methods such as ultrasonic technology is an effective step towards preserving the environment and sustainability of modern agriculture.